Intrusive Growth of Phloem Fibers in Flax Stem: Integrated Analysis of miRNA and mRNA Expression Profiles - Gorshkov, Oleg (Plants (Basel), 2019)
Phloem fibers are important elements of plant architecture and the target product of many fiber crops. A key stage in fiber development is intrusive elongation, the mechanisms of which are largely unknown. Integrated analysis of miRNA and mRNA expression profiles in intrusivelygrowing fibers obtained by laser microdissection from flax (Linum usitatissimum L.) stem revealed all 124 known flax miRNA from 23 gene families and the potential targets of differentially expressed miRNAs. A comparison of the expression between phloem fibers at different developmental stages, and parenchyma and xylem tissues demonstrated that members of miR159, miR166, miR167, miR319, miR396 families were down-regulated in intrusively growing fibers. Some putative target genes of these miRNA families, such as those putatively encoding growth-regulating factors, an argonaute family protein, and a homeobox-leucine zipper family protein were up-regulated in elongating fibers. miR160, miR169, miR390, and miR394 showed increased expression. Changes in the expression levels of miRNAs and their target genes did not match expectations for the majority of predicted target genes. Taken together, poorly understood intrusive fiber elongation, the key process of phloem fiber development, was characterized from a miRNA-target point of view, giving new insights into its regulation.